Current Theories of Social Cognition and Their Relation to a Dispute about Anthropological Difference - Jaroš, Filip (Teorie vědy / Theory of Science, 2018)
Th is study is inspired by the book Jak rozumíme druhým? Studie o sociálním rozumění a sdílení světa nejen u člověka (How do we understand others? On social understanding and sharing of the world in humans and other animals) by Petr Urban and pays attention to current discussions about social cognition, namely in the case of non-linguistic agents. Most prominent positions are held by the group of comparative psychologists led by M. Tomasello, stemming from the philosophers of collective intentionality, and the group around D. Leavens and K. Bard, which is related to an interactivist interpretation of social cognition. It is demonstrated that the differences in the results of empirical studies are based on the ontological commitments of individual research programs, coupled with their relation to the problem of anthropological difference. The study questions the possibility of choosing a suitable theory by the means of the philosophy of science. At the end, a reinterpretation of non-human social cognition on the basis of umwelt theory is brought out.